2021
DOI: 10.3390/genes13010011
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory MicroRNAs in Plasma and Atrial Fibrillation in the General Population: The Rotterdam Study

Abstract: Background: MicroRNAs (miRNAs), small non-coding RNAs regulating gene expression, have been shown to play an important role in cardiovascular disease. However, limited population-based data regarding the relationship between circulatory miRNAs in plasma and atrial fibrillation (AF) exist. Moreover, it remains unclear if the relationship differs by sex. We therefore aimed to determine the (sex-specific) association between plasma circulatory miRNAs and AF at the population level. Methods: Plasma levels of miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 57 publications
(101 reference statements)
1
21
0
Order By: Relevance
“…However, defining miRNA-21 expression as tissue-specific is not possible because of the ambiguity about whether its variation in patients with AF is due to its expression in the atria. In addition, as shown in Table 1 , the authors found an association between increased expression of miRNA-133a and a 2% increase in the chance of developing AF [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, defining miRNA-21 expression as tissue-specific is not possible because of the ambiguity about whether its variation in patients with AF is due to its expression in the atria. In addition, as shown in Table 1 , the authors found an association between increased expression of miRNA-133a and a 2% increase in the chance of developing AF [ 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geurts et al [ 19 ] selected 1901 participants with incident AF, of whom 42.1% were men and 57.9% were women. Compared to the men, the women were older and non-smokers and exhibited more cases of hypertension and diabetes mellitus.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Geurts et al [19] was the only study to suggest miR-4798-3p and miR-20a-5p as markers of AF. miR-4798-3p presents negative results only among males; however, the mechanisms of interaction of this miRNA with AF are still unknown, and further studies are needed to elucidate these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The critical role of this miRNA in the development of AF is evident. It highlights the probability of a diagnosis of predisposition and early intervention for AF if the expression of this miRNA is high [19]. miRNA-21 also acts on TGF-β, increasing the brotic state [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation